2019
DOI: 10.1111/jocn.15096
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer survivorship priorities for men and their partners: Delphi consensus from a nurse specialist cohort

Abstract: Aims & objectives To describe the prostate cancer survivorship experience and priorities from the perspective of prostate cancer specialist nurses. Background Specialist nurses are providing long‐term survivorship care to men and their partners however, few prostate cancer survivorship interventions are effective and priorities for nurse‐led survivorship care are poorly understood. Design A three‐round modified Delphi approach. Methods The study was conducted between 1 December 2018 and 28 February 2019 to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Consistent with our previous research, this expert panel described the current experience of prostate cancer survivorship in Australia as medically focused, not well coordinated and challenging, exacerbating the difficulty of treatment side effects and leading to unmet needs and anxiety [14,21]. The burden of prostate cancer in the individual has been well described, with the chronic nature and prolonged natural history of this disease, along with accumulated toxicities from existing and emerging treatments, exacerbating the need for survivorship guidelines [12].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Consistent with our previous research, this expert panel described the current experience of prostate cancer survivorship in Australia as medically focused, not well coordinated and challenging, exacerbating the difficulty of treatment side effects and leading to unmet needs and anxiety [14,21]. The burden of prostate cancer in the individual has been well described, with the chronic nature and prolonged natural history of this disease, along with accumulated toxicities from existing and emerging treatments, exacerbating the need for survivorship guidelines [12].…”
Section: Discussionmentioning
confidence: 65%
“…Shared management extends to respecting a patient’s wishes to engage in decision‐making around care to the extent they prefer, involves acknowledging and supporting the role family members and carers play, and requires access to patient records. Once shared and informed management decisions are made, these decisions should be supported by effective care coordination, with primary care providers and prostate cancer specialist nurses playing a central role as navigators [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are growing calls to increase the involvement of clinicians in addressing the needs of female partners through conducting regular screening and assessment to identify partners at risk of distress, and referral to appropriate psychosocial supports, as part of PCa survivorship care (Hyde et al., 2018). Prostate Cancer Specialist Nurses (PCSNs) are uniquely placed to play an important role in coordinating survivorship care for these women (Ralph et al., 2020). Workforce training that includes education around the psychosocial needs of female partners may help support PCSNs to bring female partners in from the periphery of the health system.…”
Section: Discussionmentioning
confidence: 99%
“…A nurse-patient collaboration project supported by the United Kingdom Oncology Nursing Society (n = 50 nurses and 18 patients) showed a high level of consensus on research related to prevention, screening, early diagnosis, and psychological care across the cancer trajectory (3). Research needs and priorities have been identified in the area of breast cancer (4), kidney research (5), expert panels, or caregivers (6), and prostate cancer survivorship (7) through Delphi consensus. In lung cancer care there is only a small-scale (n = 42) survey of health professionals in Australia, highlighting that reducing the time from presentation of symptoms to diagnosis and treatment was the highest priority while other priorities included timely referral to palliative care or unmet needs in vulnerable populations (8).…”
Section: Introductionmentioning
confidence: 99%